Bible Education That Transforms Lives in a Literacy Approach (Global Journal of Human-Social Science, 2025)
Due to the pandemic people began to have different needs and interests than they were used to and felt a need for guidance on what to think and what to do both individually and collectively They began to question pre-established concepts in various social sectors seeking satisfactory answers that would lead them to a stable and significant quality of life in both the short and long term Is it possible to promote this type of guidance today What can work to achieve this goal This article shows that Jehovah s Witnesses use a literacy approach - Critical Literacy CL in their teaching of the Bible with the aim of leading students to constant reassessment and building themselves anew paving a path for action transformation and protagonism This process of protagonism involves forming a critical consciousness in the student and moving them towards positive changes in both the short and long term Inserted with this approach Jehovah s Witnesses have used rhetorical questions and opinions in one of their study publications called Enjoy Life Forever In this material in addition the questions there are videos and illustrations that help students empathize with other contexts and similar situations giving them the opportunity to learn answers and solutions to their questions and problems However the use of the Critical Literacy approach does not in itself guarantee the achievement of educational objectives Because to get what you want you need the student s desire curiosity emotion and attention Each student has their own rhythm and time for action and transformation According to data from the JW ORG website there is both a demonstration of a point in the publication of the study from the perspective of literacy addressed and how it is conducted as well as a real case of action transformation and protagonism This article brings real possibilities for innovative education
Keywords: education; critical literacy; bible; jehovah’s witnesses; protagonism